INFLUENCE OF CHARACTERISTICS AND ROLES OF ADMINISTRATORS ON THE LOCAL MANAGEMENT EFFECTIVENESS OF ADMINISTRATORS OF LOCAL GOVERNMENT ORGANIZATIONS IN UPPER NORTHERN REGION - หมั่นการ, วิพัฒน์; บุตรน้อย, นันทะ; ทิพย์วิวัฒน์พจนา, สุธีรา (Academic Journal Phranakhon Rajabhat University, 2019)
The research purposes were to study 1) the local management effectiveness of administrators of the local government organizations in upper northern region, 2) the relationship between the characteristics and roles of administrators with the local management effectiveness of administrators of the local government organizations in upper northern region, and 3) the influence of characteristics and roles of administrators on the local management effectiveness of local administrators of the local government organizations in upper northern region. The study used quantitative research methods. The population was the chief administrator of local administrative organizations in the upper northern region. The samples were selected by stratified random sampling and determined the sample size using the table of Krejcie and Morgan at a 95% confidence level, and a 5% discrepancy was obtained with a sample of 265. A questionnaire with the reliability of 0.93 was a tool that was used to collect data. Data were analyzed using descriptive statistics such as frequency, percentage, mean, standard deviation, and inferential statistics such as Pearson's product-moment correlation analysis, and multiple regression analysis. The research found that 1) The local management effectiveness of administrators of the local government organizations was at a high level ( = 3.45, S.D. = 0.40), 2) The characteristics and roles of administrators correlated with the local management effectiveness of administrators of the local government organizations, with statistical significance at the level of 0.01, and 3) The characteristics of administrators (CA) and the roles of administrators (RA) had a positive influence on the local management effectiveness of the local government administrators (EA), with statistical significance at the level of 0.01, and the prediction equation was EAβ = 0.454CA + 0.321RA